Changes in contents of carbon, nitrogen, C:N ratio and weight loss of different substrates during cultivation of Pleurotus sajor-caju (Fr.) Singer - Gupta, Moni; Sarkar, C R; Gupta, Sachin (Mushroom Research, 2015)
Please see the full text